Spontaneous Coronary Artery Dissection - Jackson, Robert; Al-Hussaini, Abtehale; Joseph, Shiju; van Soest, Gijs; Wood, Alice; Macaya, Fernando; Gonzalo, Nieves; Cade, Jamil; Caixeta, Adriano; Hlinomaz, Ota; Leinveber, Pavel; O’Kane, Peter; et al. (JACC. Cardiovascular imaging, 2019)
This study used optical coherence tomography to investigate the mechanism of false lumen (FL) formation in spontaneous coronary artery dissection (SCAD) by studying: 1) differences between fenestrated and nonfenestrated SCAD; 2) vasa vasorum density; and 3) light attenuation characteristics of the FL. SCAD is an increasingly recognized cause of acute coronary syndromes, characterized by FL formation and compression of the true lumen (TL). The mechanisms underlying FL formation remain poorly understood. A total of 65 SCAD patients (68 vessels) who underwent acute OCT imaging as part of routine clinical care were included. Images were classified by the absence or presence of a connection (fenestration) between the TL and FL. Indexed measurements of TL stenosis, external elastic lamina (EEL) area, FL area, and light attenuation of the FL were assessed. Vasa vasorum densities of SCAD cases were compared with those in control non-SCAD myocardial infarction cases. In nonfenestrated cases, there was significantly larger expansion of the EEL area (9.1% vs. −1.9%; p <0.05) and a larger FL area (73.6% vs. 53.2%, respectively; p <0.05) in dissected segments. No significant differences were found between vasa vasorum density in SCAD and those in control subjects. The FL contents were heterogeneous but attenuated less light than whole blood or thrombus (4.28 ± 0.55 mm−1 vs. 5.08 ± 0.56 mm−1; p < 0.05; vs. 4.96 ± 0.56 mm−1; p < 0.05). These observational data suggest that the absence of a fenestration leads to increased FL pressure and compression of the TL. Although vasa vasorum may still be implicated in pathogenesis, increased vasa vasorum density could be an epiphenomenon of vascular healing. [Display omitted]